Morphometric analysis of osteonal architecture in bones from healthy young human male subjects using scanning electron microscopy - Pazzaglia, Ugo E (Blackwell Science Inc, 2013)
The shape and structure of bones is a topic that has been studied for a long time by morphologists and biologists with the goal of explaining the laws governing their development, aging and pathology. The osteonal architecture of tibial and femoral mid-diaphyses was examined morphometrically with scanning electron microscopy in four healthy young male subjects. In transverse sections of the mid-diaphysis, the total area of the anterior, posterior, lateral and medial cortex sectors was measured and analysed for osteonal parameters including osteon number and density, osteon total and bone area and vascular space area. Osteons were grouped into four classes including cutting heads (A), transversely cut osteons (B), longitudinally cut osteons (C) and sealed osteons (D). The morphometric parameters were compared between the inner (endosteal) and outer (periosteal) half of the cortex. Of 5927 examined osteons, 24.4% cutting heads, 71.1% transversely cut osteons, 2.3% longitudinally cut osteons and 2.2% sealed osteons were found. The interosteonic bone (measured as the area in a lamellar system that has lost contact with its own central canal) corresponded to 51.2% of the endosteal and 52.4% of the periosteal half-cortex. The mean number of class A cutting heads and class B osteons was significantly higher in the periosteal than in the endosteal half-cortex (P < 0.001 and P < 0.05, respectively), whereas there was no significant difference in density. The mean osteon total area, osteon bone area and vascular space area of both classes A and B were significantly higher (P < 0.001 for all three parameters) in the endosteal than in the periosteal half-cortex. The significant differences between the two layers of the cortex suggest that the osteoclast activity is distributed throughout the whole cortical thickness, with more numerous excavations in the external layer, but larger resorption lacunae closer to the marrow canal. A randomly selected population of 109 intact class B osteons was examined at higher magnification (350×) to count osteocyte lacuna and to analyse their relationship with osteon size parameters. The distribution frequency of the mean number of osteocyte lacunae increased with the increment in the sub-classes of osteon bone area, whereas the density did not show significant differences. The number of osteocyte lacunae had a direct correlation with the osteon bone area and the mean osteon wall thickness, as well as the mean number of lamellae. The osteocyte lacunae density showed an inverse relationship. These data suggest a biological regulation of osteoblast activity with a limit to the volume of matrix produced by each cell and proportionality with the number of available cells in the space of the cutting cone (total osteon area). The collected data can be useful as a set of control parameters in healthy human bone for studies on bone aging and metabolic bone diseases.